THE ANALYSIS OF WORD FORMATION PROCESS USED BY AUTISTIC CHILD - Aulia Rizki; Jufrizal Jufrizal (Universitas Negeri Padang, 2016)
This article discuss about Word formation that conceived of as the process by which words are brought into existence. This suggests that words do not exist in a vacuum; they are usually composed. This research examines autistic child in SLB Padang as a participant in conversation activity who use word formation process when communicate with other. Conversation activity was used to collect data about word formation process used by autistic child and also qualitative and descriptive method to describe and explain the processes of word formation used by autistic child. the aim of this paper to discover the word formation process used by autistic child when communicating with people especially when the teacher in the teaching and learning process in schools. From a linguistic point, an autistic child is a child who has limitations in the areas of socialization and communication. The processes of word formation were analyzed by morphological studies. The formation processes of autistic children found word in a conversation with the teacher, namely: derivation, reduplication, acronym and initialism, borrowing, clipping, compounding and blending. From the data analysis found that the dominant word formation process used autistic child is a derivation. The data used was conversation between teacher and autistic child were recorded and transcribed when the process of teaching and learning in class. The collected data are grouped based on the process of forming words.